The Internal Working Environment During Covid 19 Virus Period And Its Reflection On The Management And Organization Of The Classroom For Professors Of Physical Education And Sports In Secondary Stage - Achour , Toufik (sports creativity, 2025)
This study basically aimed to reveal to what extent teachers are able to control class, especially when internal work environment conditions are not appropriate including lack of play or training areas, a large number of pupils and covered sports halls in which air conditioning is not adequate at all, especially during corona pandemic, These latter present a big constant fear to institutions educational family, In this study we used the descriptive approach, while our research community is represented by 125 professor of physical education in the secondary education stage of Bouira province, in terms of statical methods we used percentages and (X2), The most interesting achieved result is that internal work environment affects teachers and their global performance